2016
DOI: 10.5194/isprsannals-iii-7-227-2016
|View full text |Cite
|
Sign up to set email alerts
|

Forest Area Derivation From Sentinel-1 Data

Abstract: ABS TRACT:The recently launched Sentinel-1A provides the high resolution Synthetic Aperture Radar (SAR) data with very high temporal coverage over large parts of European continent. Short revisit time and dual polarization availability supports its usability for forestry applications. The following study presents an analysis of the potential of the multi-temporal dual-polarization Sentinel-1A data for the forest area derivation using the standard methods based on Otsu thresholding and K -means clustering. Sent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 13 publications
0
7
1
Order By: Relevance
“…Mapping approaches based on Sentinel-1 SAR (time series) data have been proposed for classifying urban areas [3], general land cover classes [4,5]; forests [6][7][8][9][10]; water bodies or flooding [11][12][13] and croplands/grasslands [14,15]. Also, some recent studies on tropical forest monitoring are based on L-band data (e.g., [16,17]).…”
Section: Introductionmentioning
confidence: 99%
“…Mapping approaches based on Sentinel-1 SAR (time series) data have been proposed for classifying urban areas [3], general land cover classes [4,5]; forests [6][7][8][9][10]; water bodies or flooding [11][12][13] and croplands/grasslands [14,15]. Also, some recent studies on tropical forest monitoring are based on L-band data (e.g., [16,17]).…”
Section: Introductionmentioning
confidence: 99%
“…Forest area mapping for relatively small areas based on Sentinel-1 data was recently addressed in several studies. Overall accuracies of 94% were found over study area in North-East China [31], 92% over study area in Lower Austria [30], and balanced accuracies between 80% and 93% were reported for six sites distributed worldwide [14]. Forest type (coniferous/broadleaf) classification using Sentinel-1 was tested in two test sites in Switzerland [15] with overall accuracy of 86%.…”
Section: Performance Of the Sentinel-1 Based Forest Mapsmentioning
confidence: 99%
“…For example, a study covering five areas from Alaska to Indonesia [14] revealed that the mean accuracy increases from 77% when using single Sentinel-1 scene to 87% when using mean and standard deviation of VV and VH backscatter computed over one year of acquisitions. Similarly, overall accuracies of 92% were achieved over Austria when using parameters derived from the entire leaf-off season [30]. A different approach was introduced in [31], where only three Sentinel-1 acquisitions were used for forest mapping; these were, however, chosen to capture the conditions before, during and after the freezing period.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have proved that mapping forests using SAR data was feasible and accurate [7,30,31]. In this study, Sentinel-1 SAR data were employed to produce the forest map as the baseline for further assessing the effect of textures on classifying rubber plantations from natural forests.…”
Section: Forests Mappingmentioning
confidence: 99%